Recent trends in education and unemployment in Trinidad and Tobago - Camejo, Acton M. (1977)
Looks briefly at some trends in unemployment, within the last decade, among persons with differnet levels of education. Examines the nature of unemployment among school leavers with different types and levels of education at two points in time viz. 1974 and 1977.